2016
DOI: 10.1002/ctpp.201500111
|View full text |Cite
|
Sign up to set email alerts
|

Electric Charge of Dust Particles in a Plasma

Abstract: The problem of calculation of the electric charge of dust particles in a plasma is considered from different points of view. At first the charging of polarizable dust particles is studied within the orbital motion limited approach. Secondly, the plasma electrodynamics is applied to show that the electric charge of a dust particle is determined by the normal component of the dielectric displacement vector near the grain surface rather than the normal component of the electric field strength. And, finally, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…That the material of the dust grain is a perfect absorber is much harder to handle but is still possible in the framework of the chemical model of dusty plasmas proposed in Davletov et al. (2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That the material of the dust grain is a perfect absorber is much harder to handle but is still possible in the framework of the chemical model of dusty plasmas proposed in Davletov et al. (2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that the plasma electrodynamics in the framework of the density-response formalism provides the following interaction model of dusty plasma particles (Davletov et al. 2016): where the subscripts take on values of for electrons, for protons and for dust grains, , and , , and with the exponential integral function . In formulas (3.1) and (3.2) the distance is measured between the surfaces of the particles.…”
Section: Dust Grain Chargementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the Yukawa one‐component plasma model, those important results have one major drawback—there is no simple and practically overseen expression for the interaction potential between dust particles. In the meantime, stemming from the linear density‐response formalism, the following simplified model potential was recently proposed in to take into account the finite size of dust particles and the screening phenomenon: Φr=Znormald2e2r+2RZnormald2e2r1expitalicrknormalDknormalDRBr, where Br=expknormalD2R+rEiknormalD2R+rexpknormalD2RrEi2knormalDR+expknormalD2R+rEi2knormalDREiknormalD2R+r, with the exponential integral function Eix=xexpt/tdt and the wavenumber knormalD…”
Section: Static Propertiesmentioning
confidence: 99%